PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN PENGATURAN KERJA FLEKSIBEL TERHADAP KOMITMEN ORGANISASI DENGAN KESEIMBANGAN KEHIDUPAN & PEKERJAAN SEBAGAI MEDIATOR DALAM PERUSAHAAN STARTUP - Shelvy Kurniawan; Melki Joe (Bisnis-Net, 2026)
Technological developments and globalization have driven significant changes in the workplace, particularly in the dynamic and innovative startup sector. This growing ecosystem creates opportunities for researchers to understand how startups manage human resources amidst increasing global competition and challenges. The research method used is quantitative, with primary data sources drawn directly from respondents by distributing questionnaires to startup employees. The data collection technique used was purposive sampling. The population and unit of analysis in this study were employees working at startup companies in the Greater Jakarta area. Structural equation modeling (SEM) was used as the data analysis method. The results of this study indicate that transformational leadership and flexible work arrangements have a positive effect on work-life balance and employee commitment. Although work-life balance only mediates the effect of flexible work arrangements, it does not mediate the effect of transformational leadership on employee commitment. The practical implication is that it can help organizations increase employee loyalty and retention by creating a flexible, balanced work environment that values well-being and is led by a transformational leadership style.